Safety and Immunogenicity of Typhoid Fever and Yellow Fever Vaccines When Administered Concomitantly With Quadrivalent Meningococcal ACWY Glycoconjugate Vaccine in Healthy Adults. Issue 1 (13th October 2014) - Alberer, Martin; Burchard, Gerd; Jelinek, Tomas; Reisinger, Emil; Beran, Jiri; Hlavata, Lucie Cerna; Forleo‐Neto, Eduardo; Dagnew, Alemnew F.; Arora, Ashwani K.
<x xml:space="preserve">Abstract</x> Background Compact and short pre‐travel immunization schedules, which include several vaccinations in a single visit, are desirable for many travelers. However, concomitant vaccination could potentially compromise immunogenicity and/or safety of the individual vaccines and, therefore, possible vaccine interferences should be carefully assessed. This article discusses the immunogenicity and safety of travel vaccines for typhoid fever (TF) and yellow fever (YF), when administered with or without a quadrivalent meningococcal glycoconjugate ACWY‐CRM vaccine (MenACWY‐CRM). Methods Healthy adults (18–≤60 years) were randomized to one of three vaccine regimens: TF + YF + MenACWY‐CRM (group I; n = 100), TF + YF (group II; n = 101), or MenACWY‐CRM (group III; n = 100). Immunogenicity at baseline and 4 weeks post‐vaccination (day 29) was assessed by serum bactericidal assay using human complement (hSBA), enzyme‐linked immunosorbent assay (ELISA), or a neutralization test. Adverse events (AEs) and serious adverse events (SAEs) were collected throughout the study period. Results Non‐inferiority of post‐vaccination geometric mean concentrations (GMCs) and geometric mean titers (GMTs) was established for TF and YF vaccines, respectively, when given concomitantly with MenACWY‐CRM vaccine versus when given alone. The percentages of subjects with seroprotective neutralizing titers against YF on day 29 were similar in groups I and II. The antibody responses to meningococcal serogroups A, C, W‐135, and Y were within the same range when MenACWY‐CRM was given separately or together with TF and YF vaccines. The percentage of subjects reporting AEs was the same for TF and YF vaccines with or without MenACWY‐CRM vaccine. There were no reports of SAEs or AEs leading to study withdrawals. Conclusions These data provide evidence that MenACWY‐CRM can be administered with typhoid Vi polysaccharide vaccine and live attenuated YF vaccine without compromising antibody responses stimulated by the individual vaccines. MenACWY‐CRM can, therefore, be incorporated into travelers' vaccination programs without necessitating an additional clinic visit (NCT01466387).